Association of serum Clara cell protein CC16 with respiratory infections and immune response to respiratory pathogens in elite athletes - Kurowski, M.; Jurczyk, J.; Jarzebska, M.; Moskwa, S.; Makowska, J. S.; Krysztofiak, H.; Kowalski, M. L. (Respiratory Research, 2014)
Respiratory epithelium integrity impairment caused by intensive exercise may lead to exercise-induced bronchoconstriction. Clara cell protein (CC16) has anti-inflammatory properties and its serum level reflects changes in epithelium integrity and airway inflammation. This study aimed to investigate serum CC16 in elite athletes and to seek associations of CC16 with asthma or allergy, respiratory tract infections (RTIs) and immune response to respiratory pathogens.